2002
DOI: 10.1097/01.mp.0000018979.68686.b2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Pattern of MLH1/MSH2 Expression Is Related to Clinical and Pathological Features in Colorectal Adenocarcinomas with Microsatellite Instability

Abstract: Detection of colorectal carcinomas with highfrequency microsatellite instability (MSI-H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 33 publications
4
89
0
1
Order By: Relevance
“…MSI analysis was conducted through the use of sequence analyzers (Beckman or ABI PRISM377, Applied Biosystems). In most MSI-H cases, immunohistochemical expression of MMR proteins (MLH1, MSH2, and MSH6) was analyzed as previously reported (25,28). Constitutional mutations in MMR genes were searched through direct sequencing on DNA extracted from blood lymphocytes (25).…”
Section: Methodsmentioning
confidence: 99%
“…MSI analysis was conducted through the use of sequence analyzers (Beckman or ABI PRISM377, Applied Biosystems). In most MSI-H cases, immunohistochemical expression of MMR proteins (MLH1, MSH2, and MSH6) was analyzed as previously reported (25,28). Constitutional mutations in MMR genes were searched through direct sequencing on DNA extracted from blood lymphocytes (25).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis of MLH1 protein expression is a simple and easy way to detect MMR deficiency, and its reliability has been investigated previously (24). In the present study, immunohistochemistry of MLH1 was performed as a reliable method to detect MMR deficiency.…”
Section: Histological Response To -----------------------------------mentioning
confidence: 99%
“…Numerous studies have shown that immunohistochemistry for MMR protein expression is highly sensitive and specific for MSI, 8,10,11,[24][25][26][27][28][29][30][31] including 100% sensitivity in sporadic microsatellite instable colorectal carcinoma and approximately 90% sensitivity in familial cases, with 100% specificity in all cases when appropriate internal and external controls are employed.…”
mentioning
confidence: 99%